'Ray Ruby' Grapefruit Affected by Huanglongbing I. Planting Density and Soil Nutrient Management - Phuyal, Dinesh; Rodrigues Nogueira, Thiago Assis [UNESP]; Jani, Arun D.; Kadyampakeni, Davie M.; Morgan, Kelly T.; Ferrarezi, Rhuanito Soranz (Amer Soc Horticultural Science, 2020)
Huanglongbing (HLB), or citrus greening disease, affects practically all fruitbearing trees in commercial citrus orchards in Florida with no cure identified yet. High-density plantings and enhanced nutritional programs such as application of controlled-release fertilizer (CRF) with higher micronutrient levels can mitigate disease symptoms and extend the tree life span of sweet oranges (Citrus sinensis). The objective of this study was to evaluate the effects of tree planting density and application of CRF blends differing in N to K ratio and micronutrient content on grapefruit (Citrus paradise) plant health, canopy volume, fruit yield, and fruit quality in an HLB-affected orchard. A study was conducted in Florida for two growing seasons (2017-18 and 2018-19) to evaluate the response of 'Ray Ruby' grapefruit on Kuharske citrange (Citrus sinensis X Poncirus trifoliata) to three planting densities (300, 440, and 975 trees per ha) and two CRF blends [12 nitrogen (N)-1.31 phosphorus (P)-7.47 potassium (K) and 16N-1.31P-16.6K1 with different nutrient sources and composition. According to quantitative real-time polymerase chain reaction testing, all sampled trees tested positive for Candidatus Liberibacter asiaticus, the pathogen associated with HLB. Trees planted at 975 trees per ha had 33% lower canopy volume per tree but 160% greater fruit yield per hectare and 190% higher yield of solids compared with 300 trees per ha. Fruit produced in high-density planting (975 trees per ha) was 18% more acidic with higher soluble solid compared with low-density planting (300 trees per ha). The use of a CRF blend with higher amounts of micronutrients along with lower K increased canopy volume in both seasons and resulted in 24% and 29% reduction in fruit yield per hectare and yield of solids, respectively, in 2017-18. Our results indicate that high-density plantings increase fruit yield per area, and regardless of the N to K ratio, the use of CRF blends supplemented with micronutrients may not increase fruit yield in HLB-affected grapefruit.
Keywords: controlled-release fertilizer; fruit quality; fruit yield; planting spacing; tree health